Corinthian and Attic vases in the Detroit Institute of Arts : geometric, black-figure, and red-figure - Madigan, Brian Christopher. (Monumenta Graeca et Romana, 2008)
The collection of Greek vases in the Detroit Institute of Arts has been compiled over the course of the twentieth century to reflect the range of painting styles and shapes which characterize the period from the eighth through fourth centuries B.C. This catalogue is the first publication of that collection, comprising those vases from Corinth and Athens with painted decoration. The physical and painted characteristics of each vase are recorded, with an attribution to a painter or group, and a date. The relationship of the painted decoration to other Greek painted vases, religious or social institutions is discussed. The catalogue will be of interest to specialists in Greek vase painting, and those interested in Greek art and its modern collecting.